PENGEMBANGAN MEDIA BIG BOOK DENGAN METODE SAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Dian Octorina; Ngatmini; Dini Rakhmawati (STKIP Subang, 2023)
The problem in this study is the lack of development of learning media. The aim is to determine the validity, practicality, and effectiveness of big book media using the SAS method to improve the beginning reading skills of grade 1 elementary school students. This research is research and development with a design from Borg and Gall 10. The validity test was carried out by experts with a score of 90% for the material aspect and 90% for the learning media aspect, both of which are in the very valid category. The practicality test was obtained from student and teacher questionnaires which were stated to be practical by students by obtaining an average score of 87.25 in the very good category and the practicality/readability response of practitioners by the class teacher obtained a score of 88 in the very good category. Based on peer assessment, scores obtained with intervals of 85 are in the very good category. The result of the paired sample t test is 0.000. The n gain value obtained is 0.50 with the moderate improvement category. The results of the research show that the big book media with the SAS method developed is proven to be valid, practical, and effective so that it is very suitable for use in learning Indonesian in elementary schools to improve the beginning reading skills of grade 1 elementary school students.